If : f(x)=x^{(x+1)}\times (x+2)x^{(x+3)} Calculate : f(0)-f(-1)+f(-2)-f(-3)

dhiab May 2009 596 31 ALGERIA May 23, 2010 #1 If : \(\displaystyle f(x)=x^{(x+1)}\times (x+2)x^{(x+3)}\) Calculate : \(\displaystyle f(0)-f(-1)+f(-2)-f(-3)\)

If : \(\displaystyle f(x)=x^{(x+1)}\times (x+2)x^{(x+3)}\) Calculate : \(\displaystyle f(0)-f(-1)+f(-2)-f(-3)\)

D dwsmith MHF Hall of Honor Mar 2010 3,093 582 Florida May 23, 2010 #2 dhiab said: If : \(\displaystyle f(x)=x^{(x+1)}\times (x+2)x^{(x+3)}\) Calculate : \(\displaystyle f(0)-f(-1)+f(-2)-f(-3)\) Click to expand... \(\displaystyle x^{x+1}x^{x+3}=x^{x+1+x+3}=x^{2x+4}\) \(\displaystyle x^{2x+4}(x+2)=x^{2x+4}x+2x^{2x+4}=x^{2x+4+1}+2x^{2x+4}=x^{2x+5}+2x^{2x+4}\)

dhiab said: If : \(\displaystyle f(x)=x^{(x+1)}\times (x+2)x^{(x+3)}\) Calculate : \(\displaystyle f(0)-f(-1)+f(-2)-f(-3)\) Click to expand... \(\displaystyle x^{x+1}x^{x+3}=x^{x+1+x+3}=x^{2x+4}\) \(\displaystyle x^{2x+4}(x+2)=x^{2x+4}x+2x^{2x+4}=x^{2x+4+1}+2x^{2x+4}=x^{2x+5}+2x^{2x+4}\)

D dwsmith MHF Hall of Honor Mar 2010 3,093 582 Florida May 23, 2010 #4 wonderboy1953 said: I think natural logs will help you out. Click to expand... Why not just plug in the values? \(\displaystyle 0^4=0\)

wonderboy1953 said: I think natural logs will help you out. Click to expand... Why not just plug in the values? \(\displaystyle 0^4=0\)